Export impact on dividend policy for big Colombian exporting firms, 2006-2014 - Federico Alberto Merchan Alvarez (Kiel Institute for the World Economy (IfW Kiel), 2023)
This paper studies the impact of exogenous export demand shocks on firms' dividend policy using firm specific real exchange rate variation as instrumental variable. IV exclusion restriction is plausibly satisfied because real exchange rate shocks were unanticipated -partly explained because of international oil price fluctuation-, and first stage results confirm relevance condition fulfillment. The results indicate that big private Colombian exporting firms decree dividends as a way to mitigate the agency cost generated by exogeneous exports variation via higher free cash flow and cash flow volatility, especially in poor managerial quality firms. Evidence supports agency cost theory and denies signaling.
Keywords: F14; F10; G30; G32; G14; G35; 330; dividends; exports; agency cost; free cash flow; volatility